Podle vůně poznáte je.: Individuální rozpoznávání čichem - Havlíček, Jan (Lidé města, 2004)
A number of mammalian species discriminate their mates by their smell. Humans also produce temporarily stable odour signatures. The results of several studies showed that humans are able to recognise their own odour, the odour of their partner or relatives. Also the unfamiliar subjects can match the odour of children and their mothers, but not the odour of spouses. This suggests that as on visual level, the odour of individual relatives resembles each other, probably due to genetic factors. Odour communication is a powerful tool in very early infant´s life already. A newborn can find the nipple and recognise its mother within a few hours after birth. A mother is also able to identify the smell of her infant even when her contact with the baby was restricted to several hours. Studies on gender judgments by smell found that the more intense and unpleasant smells are mostly attributed to men and vice versa. Thus gender is presumably not perceived per se by smell, but rather by perceived intensity. The aim of this paper is to critically review studies on human odour recognition and to propose the directions of future research.